ANALISIS SISTEM PENGUPAHAN KARYAWAN HOME INDUSTRI TOGE AN PERSPEKTIF ETIKA BISNIS ISLAM - daryoto; Ainun Mardhiyah (Al-Idarah, 2025)
Employee wage payments at Home Industry Toge AN have problems regarding the full linkage between employee wages and the results of bean sprout sales each month. With this full linkage, the relationship between business owners and employees does not go well, this is because one party feels disadvantaged, namely the employee. This study aims to analyze the employee wage system using Islamic Business Ethics. The focus of the problem in this study is as follows: how is the practice of the employee wage system at Home Industry Toge AN, Delta Pawan District, Ketapang Regency, West Kalimantan? and how is the analysis of Islamic business ethics on the employee wage system at Home Industry Toge AN, Delta Pawan District, Ketapang Regency, West Kalimantan?. In this study, the approach used by the researcher is a descriptive qualitative approach using the type of field research (Field Research), this study was conducted using the interview method with business owners and employees who work at Home Industry Toge AN, Delta Pawan District, Ketapang Regency, West Kalimantan. The results of this study are that in the AN Toge Home Industry, Delta Pawan District, Ketapang Regency, West Kalimantan, in practice it is not in accordance with the principles of Islamic business ethics, namely in the employee wage system which is fully related to the results of bean sprout sales and Islamic business ethics related to the principle of justice. Meaningful justice is clearly not in accordance with the concept of wages, because employee wages are linked to the results of bean sprout sales, so that wages change every month.